Skin diseases affecting the vulva. Issue 3 (March 2017) - Simpson, Rosalind; Nunns, David
Abstract: Vulval skin disease is common in gynaecological practice. This review aims to enhance clinical skills in patient assessment, vulval examination and treatment of common benign vulval skin disease. Basic treatments are often of benefit the patient (e.g. use of emollients and topical steroids), but many patients have complex disease and can present with more than one condition so careful assessment and individualised management is essential. Understanding of when to refer onwards to a vulval specialist service is important to optimize clinical outcomes. Clinical outcomes to consider for all patients with vulval skin disease should include: (i) a reduction in symptoms (e.g. less itch, fewer flare-ups); (ii) an improvement in function (e.g. sexual function, mobility); (iii) increased confidence in self-management (e.g. management of flare-ups and self-examination).